INCREASING STUDENT INTEREST THROUGH THE ENCYCLOPEDIA MEDIA OF CLASSIFICATION OF LIVING THINGS IN SCIENCE INSTRUCTION - Zulfah Zulfah; Adilah Endah Putriyani (Jurusan Tarbiyah dan Pendidikan, 2021)
Abstract Science instruction with conceptual material is often less attractive to students. It’s considered less attractive and difficult to understand than it’s necessary to develop interactive learning media for instruction. This study aims to develop the media and see its effect on increasing student interest in science instruction by using the Encyclopedia of Classification of Living Things through the demonstration method. This research was conducted on grade VII students at Madrasah Tsanawiyah 4 Ponorogo in the 2019/2020 school year. The type of research used is descriptive quantitative research. Data collection by filling out a questionnaire to measure students' interest in instruction. The results showed that there was an increase in student interest in instruction after using the Encyclopedia Media of Classification of Living Things. The average value obtained from before instruction was 74.76 while the average score obtained of post instruction was 75.52. Based on the analysis of these data, it can be concluded that there is an increase in student interest in science instruction by using encyclopedia media in classification of living things material. Keywords: Learning interest; natural science instruction; media